Federated States of Micronesia : 2021 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Federated States of Micronesia. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2021)
The COVID-19 pandemic and related containment measures have put severe strains on the economy. The economic policy response has been strong and generally appropriate, helping counter the negative effects of the pandemic. Nevertheless, as the international borders remain shut, the economic contraction is likely to deepen in FY2021. A slow recovery is expected for FY2022 driven by a gradual border reopening. The FSM is facing significant medium-term uncertainty, owing to the possible expiration of grants and other assistance provided under the Compact Agreement with the United States. The FSM is also highly vulnerable to climate change-induced natural disasters.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: International Agreements and Observance; International Organizations; Monetary Policy